Isolated Paralysis of the Adductor Pollicis: A Case Report - F. De Maio; S. Bisicchia; P. Farsetti; E. Ippolito (Advances in Orthopedics)
We report a case of isolated paralysis of the right adductor pollicis in a 30-year-old woman. Electromyographic study showed involvement of the deep motor branch of the ulnar nerve. A ganglion and an anomalous muscle were both ruled out clinically and by MRI as a possible cause of the paralysis. At surgical exploration, we found a fibrous band joining the pisiform and the hook of the hamate bone that compressed the deep motor branch of the ulnar nerve. The fibrous band was excised, and a neurolysis of the motor branch of the ulnar nerve was performed. At followup, eight months later, the patient had fully recovered strength of the adductor muscle.